Potensi Retribusi Parkir dan Pajak Restoran di Kawasan Wisata Kuliner Baiman Banjarmasin - Khansa, Ridha Muthia; Nuryadin, Muhammad Rusmin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
The purpose of this research is (1) to find out how much potential restaurant taxes are in the culinary tourism area of Baiman Banjarmasin and (2) to find out how much potential parking fees are in the culinary tourism area of Baiman Banjarmasin. The study uses primary data from interviews with restaurant owners and parking lot managers in the Baiman Banjarmasin culinary tourism area. The quantitative descriptive method is used in this study. The results of this study indicate that the restaurant tax in the culinary area of Baiman Banjarmasin has considerable potential for regional income. The calculation of parking fees in the culinary area of Baiman Banjarmasin also has enormous potential if managed optimally by the Banjarmasin city government, especially the Banjarmasin city parking UPTD.